Facile Access to Structurally Diverse Antimalarial Indoles Using a One-Pot A3 Coupling and Domino Cyclization Approach - da Silva, Gustavo (2023)
Funding Information: . The authors acknowledge the financial support provided by Fundação para a Ciência e a Tecnologia (FCT Portugal) through the PhD grant research project SFRH/BD/103412/2014 and projects PTDC/MED‐QUI/30021/2017, PTDC/MED‐CAR/31322/2017 and PTDC/SAU‐TOX/32515/2017, and the research unit GHTM (UID/Multi/04413/2013 and GHTM‐UID/04413/2020). We thank MR4 for providing us with malaria parasites contributed by Andrew Talman, Robert Sinden Funding Information: The authors acknowledge the financial support provided by Fundação para a Ciência e a Tecnologia (FCT Portugal) through the PhD grant research project SFRH/BD/103412/2014 and projects PTDC/MED-QUI/30021/2017, PTDC/MED-CAR/31322/2017 and PTDC/SAU-TOX/32515/2017, and the research unit GHTM (UID/Multi/04413/2013 and GHTM-UID/04413/2020). We thank MR4 for providing us with malaria parasites contributed by Andrew Talman, Robert Sinden. Publisher Copyright: © 2023 Wiley-VCH GmbH.